Is it a book…is it a game? No, it is TOK - Sylla, Cristina (2011)
The interface presented here aims at helping children to create their own stories and to reflect over their narratives, in a process whereby they learn how to build logical sequences, enhancing their vocabulary and literacy. At the same time we wanted to make it easier for young children to interact with digital content, through the tangibility of the interface.